EFEKTIVITAS MODEL PEMBELAJAARAN KOOPERATIF TIPE THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI KELESTARIAN LINGKUNGAN DI SD TELLO BARU III KOTA MAKASSAR - Mursida; Erma Suryani Sahabuddin; Amrah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is based on the issue of students' conceptual understanding regarding environmental conservation material at SD Inpres Tello Baru III. The purpose of this research is to describe the implementation and effectiveness of the cooperative learning model Thinking Aloud Pair Problem Solving (TAPPS), as well as the improvement of students' conceptual understanding on environmental conservation after the application of the TAPPS model in Grade IV of SD Inpres Tello Baru III, Makassar City. This research refers to observation sheets and the results of students’ conceptual understanding tests, namely pre-test and post-test. A quantitative approach was employed in this study. The research design used is the one-group pretest-posttest design. The study was conducted at UPT SPF SD Inpres Tello Baru III, with all students as the population. The sample consisted of 25 Grade IV students. The data analysis technique used was descriptive statistical analysis. The results of the study indicate that the use of the cooperative learning model Thinking Aloud Pair Problem Solving (TAPPS) is effective in improving students' conceptual understanding of environmental conservation in Grade IV of SD Inpres Tello Baru III, Makassar City.